Lithium ion battery negative electrode material, negative electrode, preparation method of negative electrode and lithium ion battery

By mixing graphene aerogel with secondary graphite to form a stable SEI layer, the challenges of lithium-ion battery anode material in terms of cycle life and battery capacity are solved, and the battery cycle life is significantly improved and the cost is reduced.

CN119742317AActive Publication Date: 2025-04-01SHANGHAI QIYUAN EXPLORATION MATERIALS TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411930074.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

Existing lithium-ion battery anode materials have challenges in improving cycle life, especially the difficulty in meeting the rapid diffusion kinetics of lithium ions and the maintenance of battery capacity.

Method used

Graphene aerogel is used as a modifier and mixed with secondary graphite to form a uniform and stable SEI layer, thereby improving the cycle life of the battery.

Benefits of technology

Through graphene aerogel modification, the cycle life of lithium-ion batteries can be doubled while maintaining battery capacity and reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742317A_ABST
    Figure CN119742317A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, and provides a lithium ion battery negative electrode material, a negative electrode, a preparation method of the negative electrode and a lithium ion battery. The lithium ion battery negative electrode material provided by the invention comprises secondary graphite, a modifier, a conductive agent and a binder, the modifying agent is graphene aerogel. According to the invention, the graphene aerogel is used as a modifier to be added into the negative electrode material, the graphene aerogel is compatible with a commercial graphite negative electrode material matrix system in the existing lithium ion battery, and can quickly form a uniform and stable SEI layer after being mixed with secondary graphite, so that the cycle life of the battery can be doubled without influencing the capacity of the battery; and moreover, the graphene aerogel has a large number of defects, so that Li < + > adsorption can be promoted, the lithium storage capacity is greatly improved, and the cycle life is greatly prolonged. Meanwhile, the negative electrode material provided by the invention is low in cost and beneficial to large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode material for a lithium ion battery, a negative electrode and a preparation method thereof, and a lithium ion battery. Background Art

[0002] With the continuous development of the new energy field, electrochemical energy storage and the development of clean, intelligent and green energy have received more and more attention, especially for fixed energy storage power stations. Having a stable and long-term power supply is the key to meeting the requirements of energy storage power station construction. However, the dendrite problem of lithium metal will cause irreversible damage to the battery, resulting in a poor cycle life. Although electrolyte engineering is currently under vigorous research and development, its cost, process and other issues make it still not ready for full industrialization in the next few years.

[0003] As a carrier of lithium ions and electrons in the battery, the negative electrode material plays an important role in energy storage and release, directly affecting the battery's energy density, cycle life, safety, fast charging capability and other performance. At present, the most widely used negative electrode material for lithium-ion batteries is secondary graphite. The technology in this field to improve the performance of lithium-ion batteries mainly focuses on graphite surface modification. For example, graphite is modified by metal / metal oxide coating, carbon doping, etc. to improve Li + transport kinetics, and reduce the damage of lithium dendrites. However, these strategies are difficult to simultaneously meet the requirements of Li + The fast diffusion kinetics in graphite particles and the graphite surface modification may lead to low first efficiency, thus affecting the battery capacity.

[0004] Related technologies disclose a silicon-based lithium supplement modifier material, which disperses lithium-containing components on the surface or in the pores of a porous silicon matrix to achieve high-content pre-supplementation of lithium, effectively improving the initial efficiency and cycle stability of lithium-ion batteries. However, this method adds lithium-containing components to the negative electrode material, and the lithium-containing components need to be dispersed in the porous silicon matrix, which increases the overall production cost and the complexity of the production line.

[0005] In summary, there is an urgent need to develop a negative electrode material with simple composition that can effectively improve the cycle life of lithium-ion batteries. Summary of the invention

[0006] In view of this, the present invention provides a lithium ion battery negative electrode material, a negative electrode and a preparation method thereof, and a lithium ion battery. The present invention adds graphene aerogel as a modifier to the negative electrode material, which can quickly form a uniform and stable SEI layer after mixing with secondary graphite, and can double the battery cycle life without affecting the battery capacity.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] A negative electrode material for a lithium ion battery comprises the following components: secondary graphite, a modifier, a conductive agent and a binder; the modifier is graphene aerogel; and the mass ratio of the secondary graphite to the graphene aerogel is 9.5:0.5 to 0.5:9.5.

[0009] Preferably, the graphene aerogel has D / I G The value is 0.8~1.3.

[0010] Preferably, the graphene aerogel has an average particle size of 4 to 10 μm, an average pore size of 1 to 30 nm, and a BET specific surface area of ​​1 to 2000 m 2 g -1 , pore volume is 0.001~2m 2 g -1 .

[0011] Preferably, the weight ratio of the graphene aerogel to the secondary graphite is 0.5-3:7-9.5.

[0012] Preferably, the mass ratio of the total weight of the secondary graphite and graphene aerogel to the conductive agent and the binder is 6 to 8:1 to 3:1.

[0013] Preferably, the conductive agent is acetylene black; and the binder is polyvinylidene fluoride and / or polyimide.

[0014] The present invention also provides a lithium ion battery negative electrode, comprising a current collector and a negative electrode material arranged on the surface of the current collector; the negative electrode material is the lithium ion battery negative electrode material described in the above scheme.

[0015] The present invention also provides a method for preparing the negative electrode of the lithium ion battery described in the above scheme, comprising the following steps:

[0016] Mixing a lithium-ion battery negative electrode material and a solvent to obtain a negative electrode slurry;

[0017] The negative electrode slurry is coated on the surface of the current collector and then dried to obtain the negative electrode of the lithium ion battery.

[0018] Preferably, the coating method is scraping, and the scraping rate is 3 to 8 cm s -1 The coating thickness is 500-1000 μm.

[0019] The present invention also provides a lithium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the negative electrode is the lithium ion battery negative electrode described in the above scheme or the lithium ion battery negative electrode prepared by the preparation method described in the above scheme.

[0020] The present invention provides a negative electrode material for a lithium-ion battery, comprising the following components: secondary graphite, a modifier, a conductive agent and a binder; the modifier is graphene aerogel; the mass ratio of the secondary graphite to the graphene aerogel is 9.5:0.5 to 0.5:9.5. Graphene aerogel is a type of graphite, which is compatible with the existing commercial graphite negative electrode material base system in lithium-ion batteries, does not affect the electrode capacity, and can be directly used in the existing lithium-ion battery material system; graphene aerogel has a large number of edge and sheet lattice defects, which can promote Li + Adsorption greatly improves lithium storage capacity and cycle life.

[0021] Moreover, graphene aerogel as a modifier can quickly form a uniform and stable SEI layer after being mixed with secondary graphite to construct a stable negative electrode. The main principles are as follows: (1) Increasing active sites: Defects in graphene aerogel can provide more active sites, which can promote the decomposition of substances in the electrolyte, thereby accelerating the formation of the SEI layer; (2) Improving ion transport: The presence of defects can increase the specific surface area and porosity of the material, which helps to improve the transmission path of lithium ions, allowing lithium ions to pass through the SEI layer more quickly, thereby accelerating the formation of the SEI layer; (3) Promoting uniform film formation: Defects in graphene aerogel can promote the uniform distribution of additives in the electrolyte, which helps to form a uniform and stable SEI layer, thereby improving the cycle stability and safety of the battery.

[0022] In addition, the negative electrode material provided by the present invention has low cost and is conducive to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a scanning electron microscope photograph of the graphene aerogel used in the embodiment of the present invention;

[0024] Figure 2 is the Raman curve of the graphene aerogel used in the embodiment of the present invention;

[0025] Figure 3 : is the cyclic voltammetry curve of the graphene aerogel used in the embodiment of the present invention;

[0026] Figure 4 This is a scanning electron microscope photograph of the negative electrode surface of the lithium-ion battery to which graphene aerogel is added in Example 1 after 15 cycles at a current density of 1C;

[0027] Figure 5 The charge-discharge curve of the lithium-ion battery to which the graphene aerogel is added in Example 1 after the 200th cycle at a current density of 1C;

[0028] Figure 6 This is a scanning electron microscope photograph of the negative electrode surface of the lithium-ion battery to which graphene aerogel is added in Example 1 after cycling 200 times at a current density of 1C;

[0029] Figure 7 The cycle life curve of the lithium ion battery with graphene aerogel added in Example 1 compared with the commercial secondary graphite lithium ion battery at 1C current density;

[0030] Figure 8 The cycle life curve of the lithium-ion battery containing graphene aerogel in Example 2 and the commercial secondary graphite lithium-ion battery at 1C current density is shown. DETAILED DESCRIPTION

[0031] The invention provides a lithium ion battery negative electrode material, comprising the following components: secondary graphite, graphene aerogel, a conductive agent and a binder; the mass ratio of the secondary graphite to the graphene aerogel is 9.5:0.5 to 0.5:9.5.

[0032] In the present invention, the secondary graphite is commercial secondary graphite. The present invention has no special requirements on the source of the secondary graphite, and commercially available products can be used.

[0033] In the present invention, the weight ratio of the graphene aerogel to the secondary graphite is preferably 0.5-3:7-9.5, specifically 0.5:9.5, 1:9, 1.5:8.5, 2:8 or 3:7, more preferably 1:9 or 2:8.

[0034] In the present invention, the graphene aerogel has D / I G The value is preferably 1.08; the average particle size of the graphene aerogel is preferably 4 to 10 μm, specifically 5 μm, 8 μm or 9.84 μm, the average pore size is preferably 1 to 30 nm, specifically 1 nm, 1.736 nm, 2 nm, 5 nm, 10 nm or 25 nm, and the BET specific surface area is preferably 1 to 2000 m 2 g -1 , specifically 500m 2 g -1 , 1000m 2 g -1 、1500m 2 g -1 or 2000m 2 g -1 The pore volume is preferably 0.001 to 2 m 2 g -1 , specifically 0.1m 2 g -1 、0.5m 2 g -1 、0.682m 2 g -1 , 1m 2g -1 or 1.5m 2 g -1 The present invention has no special requirements on the source of the graphene aerogel, and it can be prepared by using commercial products or by methods well known to those skilled in the art, as long as the average particle size, average pore size, BET specific surface area and pore volume meet the above requirements.

[0035] In the present invention, the mass ratio of the total weight of the secondary graphite and graphene aerogel to the conductive agent and the binder is preferably 6 to 8:1 to 3:1, specifically 7:2:1, 8:1:1 or 6:3:1; the conductive agent is preferably acetylene black; the binder is preferably polyvinylidene fluoride (PVDF) and / or polyimide.

[0036] The present invention also provides a lithium ion battery negative electrode, comprising a current collector and a negative electrode material arranged on the surface of the current collector; the negative electrode material is the lithium ion battery negative electrode material described in the above scheme.

[0037] The present invention also provides a method for preparing the negative electrode of the lithium ion battery described in the above scheme, comprising the following steps:

[0038] Mixing a lithium-ion battery negative electrode material and a solvent to obtain a negative electrode slurry;

[0039] The negative electrode slurry is coated on the surface of the current collector and then dried to obtain the negative electrode of the lithium ion battery.

[0040] The present invention mixes the negative electrode material of the lithium ion battery with a solvent to obtain a negative electrode slurry. In the present invention, the solvent is preferably N-methylpyrrolidone; the mixing of the negative electrode material of the lithium ion battery with the solvent preferably includes: mixing secondary graphite, graphene aerogel and a conductive agent to obtain a mixed powder; mixing a binder and a solvent to obtain a binder solution; mixing the mixed powder and the binder solution to obtain a negative electrode slurry; the method of mixing the secondary graphite, graphene aerogel and a conductive agent is preferably solid phase homogenization; the device used for the solid phase homogenization is preferably a ball mill, a sand grinder or a disperser; the mixing time is preferably 1 to 5 hours, more preferably 1 to 3 hours; the mass ratio of the binder to the solvent is preferably 0.25 to 0.5:4.75 to 9.5, and the mixing time of the binder and the solvent is preferably 1 to 3 hours; the mixing time of the mixed powder and the binding solution is preferably 12 to 48 hours.

[0041] After obtaining the negative electrode slurry, the present invention applies the negative electrode slurry on the surface of the current collector and then dries it to obtain the negative electrode of the lithium ion battery. In the present invention, the current collector is preferably copper foil; the coating method is preferably scraping, and the scraping rate is preferably 3 to 8 cm s -1 , specifically 5 cm s -1or 6cm -1 ; The thickness of the scraping is preferably 500-1000 μm; the drying is preferably carried out by air drying and vacuum drying in sequence; the temperature of the air drying is preferably 60-90°C, and the drying time is preferably 10-30 min; the temperature of the vacuum drying is preferably 60-90°C, and the drying time is preferably 12-24 h.

[0042] The present invention also provides a lithium-ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the negative electrode is the lithium-ion battery negative electrode described in the above scheme or the lithium-ion battery negative electrode prepared by the preparation method described in the above scheme; the present invention has no special requirements for the positive electrode, separator and electrolyte, and those familiar to those skilled in the art can be used.

[0043] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] The graphene aerogel used in the following examples has an average particle size of 9.84 μm, an average pore size of 1.736 nm, and a BET specific surface area of ​​1572 m 2 g -1 , pore volume 0.682mLg -1 .

[0045] Example 1

[0046] (1) 3.6 g of commercial secondary graphite, 0.4 g of graphene aerogel and 1.14 g of acetylene black were mixed uniformly by solid phase homogenization reaction for 2 h to obtain a mixed powder.

[0047] (2) Dissolve 1 g of PVDF powder in 19 g of N-methylpyrrolidone and stir for 2 h at a speed of 1000 r / min to obtain a PVDF solution.

[0048] (3) 5.14 g of the mixed powder and 11.4 g of the PVDF solution were uniformly stirred for 24 h to obtain a negative electrode slurry.

[0049] (4) Using copper foil as the substrate, take 5 mL of negative electrode slurry using a 1000 μm scraper and squeegee at 5 cm s -1 The coating was completed at a speed of , and the electrode was quickly dried in a 90°C forced air drying oven for 20 min, and then transferred to a 90°C vacuum drying oven for drying for 12 h to obtain a negative electrode.

[0050] Performance Testing:

[0051] Figure 1 This is a scanning electron microscope photo of graphene aerogel. Figure 2 is the Raman curve of graphene aerogel. Figure 1-2 It can be seen that the graphene aerogel has a porous structure, and the Raman curve shows that the I D / I G The value is 1.08, indicating that there are a large number of defects. The presence of defects can increase the specific surface area and porosity of the material, which helps to improve the transmission path of lithium ions, allowing lithium ions to pass through the SEI layer more quickly, thereby accelerating the formation of the SEI layer.

[0052] Figure 3 is the cyclic voltammetry curve of graphene aerogel. Figure 3 It can be seen that there is no obvious current mutation in the CV curve during the potential scanning process, indicating that the graphene aerogel has good electrochemical stability.

[0053] The negative electrode prepared in Example 1 was used to assemble a lithium-ion battery for a cyclic charge and discharge test, wherein the lithium sheet was used as the positive electrode and the electrolyte was LB-1178 (1M LiPF6, DMC:EC=7:3Vol%, 5% FEC).

[0054] Figure 4 This is a scanning electron microscope image of the negative electrode surface of a lithium-ion battery with graphene aerogel added after 15 cycles at 1C current density. Figure 4 It can be seen that after only 15 cycles, the negative electrode surface can present a dense morphology, which is beneficial to improving the electrode cycle stability.

[0055] Figure 5 This is the charge-discharge curve of the lithium-ion battery with graphene aerogel added at the 200th cycle at 1C current density. Figure 5 It can be seen that the electrode surfaces all exhibit a dense, flat and smooth morphology, which is beneficial to improving the chemical cycle stability of the battery.

[0056] Figure 6 This is a scanning electron microscope image of the negative electrode surface of a lithium-ion battery with graphene aerogel added after 200 cycles at 1C current density. Figure 6 It can be seen that the surface of the negative electrode is flatter and more regular after 200 cycles, which is conducive to more uniform storage of lithium.

[0057] Figure 7 The cycle life curve of the lithium-ion battery with graphene aerogel added in Example 1 and the commercial secondary graphite lithium-ion battery at 1C current density. Figure 7 It can be seen that the capacity of lithium-ion batteries assembled with negative electrodes added with graphene aerogel can reach 365mAh g -1At the same time, the cycle life can be doubled compared to commercial secondary graphite lithium-ion batteries.

[0058] Example 2

[0059] (1) 3.2 g of commercial secondary graphite, 0.8 g of graphene aerogel and 1.14 g of acetylene black were mixed uniformly by solid phase homogenization reaction for 2 h to obtain a mixed powder.

[0060] (2) Dissolve 1 g of PVDF powder in 19 g of N-methylpyrrolidone and stir for 2 h at a speed of 1000 r / min to obtain a PVDF solution.

[0061] (3) 5.14 g of the mixed powder and 11.4 g of the PVDF solution were uniformly stirred for 24 h to obtain a negative electrode slurry.

[0062] (4) Using copper foil as the substrate, take 5 mL of negative electrode slurry using a 1000 μm scraper and squeegee at 5 cm s -1 The coating was completed at a speed of , and the electrode was quickly dried in a 90°C forced air drying oven for 20 min, and then transferred to a 90°C vacuum drying oven for 12 h to obtain a negative electrode.

[0063] A lithium-ion battery assembled with the negative electrode prepared in Example 2 was subjected to a cyclic charge and discharge test, wherein a graphite electrode was used as the negative electrode, a lithium sheet was used as the positive electrode, and the electrolyte composition was LB-1178.

[0064] Figure 8 The cycle life curve of the lithium-ion battery with graphene aerogel added in Example 2 compared with the commercial secondary graphite lithium-ion battery at 1C current density. Figure 8 It can be seen that the capacity of the lithium-ion battery assembled with the negative electrode added with graphene aerogel in Example 2 can be stabilized at 345 mAh g -1 , and the cycle life can be doubled compared to commercial secondary graphite lithium-ion batteries.

[0065] Comparative Example 1

[0066] (1) 3.6 g of commercial secondary graphite, 0.4 g of graphene powder and 1.14 g of acetylene black were mixed uniformly by solid phase homogenization reaction for 2 h to obtain mixed powder. The graphene powder was prepared by liquid phase exfoliation method, and Raman test showed that I D :I G The value is 0.25, the lamellar lattice is complete, with few defects, the average particle size is 3.65μm, and the specific surface area is 547m 2 / g.

[0067] (2) Dissolve 1 g of PVDF powder in 19 g of N-methylpyrrolidone and stir for 2 h at a speed of 1000 r / min to obtain a PVDF solution.

[0068] (3) 5.14 g of the mixed powder and 11.4 g of the PVDF solution were uniformly stirred for 24 h to obtain a negative electrode slurry.

[0069] (4) Using copper foil as the substrate, take 5 mL of negative electrode slurry using a 1000 μm scraper and squeegee at 5 cm s -1 The coating was completed at a speed of , and the electrode was quickly dried in a 90°C forced air drying oven for 20 min, and then transferred to a 90°C vacuum drying oven for drying for 12 h to obtain a negative electrode.

[0070] The negative electrode prepared in Comparative Example 1 was used to assemble a lithium-ion battery for cyclic charge and discharge tests, wherein the lithium sheet was used as the positive electrode and the electrolyte was LB-1178 (1M LiPF6, DMC:EC=7:3Vol%, 5% FEC). The experimental results show that at a current density of 1C, compared with a commercial secondary graphite lithium-ion battery, the cycle life of the lithium-ion battery assembled in Comparative Example 1 can be increased by 37%, which is lower than that of the lithium-ion battery assembled with the negative electrode added with graphene aerogel, indicating that the large number of defects in the graphene aerogel can more effectively increase the cycle life of the lithium-ion battery.

[0071] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A negative electrode material for a lithium ion battery, characterized in that: The invention comprises the following components: secondary graphite, a modifier, a conductive agent and a binder; the modifier is graphene aerogel; and the mass ratio of the secondary graphite to the graphene aerogel is 9.5:0.5 to 0.5:9.

5.

2. The negative electrode material for lithium-ion batteries according to claim 1, characterized in that: I of the graphene aerogel D / I G The value is 0.8~1.

3.

3. The negative electrode material for lithium-ion batteries according to claim 1, characterized in that: The graphene aerogel has an average particle size of 4 to 10 μm, an average pore size of 1 to 30 nm, and a BET specific surface area of ​​1 to 2000 m 2 g -1 , pore volume is 0.001~2m 2 g -1 .

4. The negative electrode material for lithium-ion batteries according to claim 1, characterized in that: The weight ratio of the graphene aerogel to the secondary graphite is 0.5-3:7-9.

5.

5. The negative electrode material for lithium-ion batteries according to claim 1, characterized in that: The mass ratio of the total weight of the secondary graphite and the graphene aerogel to the conductive agent and the binder is 6 to 8:1 to 3:

1.

6. The negative electrode material for lithium-ion batteries according to claim 1, characterized in that: The conductive agent is acetylene black; the binder is polyvinylidene fluoride and / or polyimide.

7. A negative electrode for a lithium ion battery, characterized in that: It comprises a current collector and a negative electrode material arranged on the surface of the current collector; the negative electrode material is the lithium ion battery negative electrode material according to any one of claims 1 to 6.

8. The method for preparing the negative electrode of a lithium ion battery according to claim 7, characterized in that: The following steps are involved: Mixing a lithium-ion battery negative electrode material and a solvent to obtain a negative electrode slurry; The negative electrode slurry is coated on the surface of the current collector and then dried to obtain the negative electrode of the lithium ion battery.

9. The preparation method according to claim 8, characterized in that: The coating method is scraping, and the scraping speed is 3-8 cm s -1 The coating thickness is 500-1000 μm.

10. A lithium ion battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The negative electrode is the negative electrode for a lithium ion battery according to claim 7 or the negative electrode for a lithium ion battery prepared by the preparation method according to any one of claims 8 to 9.

Citation Information

Patent Citations

  • Lithium battery negative electrode slurry with good dispersion effect and preparation method of lithium battery negative electrode slurry

    CN112072093A

  • Low-temperature-resistant lithium ion battery

    CN113540459A

  • Carbon aerogel-based electrode material and manufacturing method thereof

    CN114639818A

  • Negative electrode active material, methode for synthesis the same, and lithium rechargable battery including the same

    KR1020150117172A

  • Gel polymer lithium ion capacitor battery and electrode, and preparation method therefor

    WO2022134377A1